2015
DOI: 10.14309/crj.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

Osteopetrosis: A New Cause of Upper Gastrointestinal Bleeding

Abstract: Osteopetrosis is a genetic disorder of bone remodeling caused by osteoclast dysfunction. Clinical features include short stature, frequent fractures, and recurrent infections. Abnormal bone obliterates the marrow cavity, resulting pancytopenia and extramedullary hematopoiesis in the liver and spleen. The splenomegaly can lead to left-sided portal hypertension. We report the second case of osteopetrosis-induced portal hypertension and the first case of upper gastrointestinal bleeding in a 52-year-old woman with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Portal hypertension was primarily caused by osteopetrosis, which led to a decrease in bone marrow hematopoietic ability, followed by liver extramedullary hemopoiesis and an increase in intrahepatic resistance. In 2014, Katz et al 3 reported a 52-yearold female osteopetrosis patient with portal hypertension who presented with ascites and esophageal variceal bleeding. The author believed that the cause of portal hypertension was the decreased hematopoiesis in the bone marrow caused by osteopetrosis, and the occurrence of extramedullary hemopoiesis in the spleen resulted in splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Portal hypertension was primarily caused by osteopetrosis, which led to a decrease in bone marrow hematopoietic ability, followed by liver extramedullary hemopoiesis and an increase in intrahepatic resistance. In 2014, Katz et al 3 reported a 52-yearold female osteopetrosis patient with portal hypertension who presented with ascites and esophageal variceal bleeding. The author believed that the cause of portal hypertension was the decreased hematopoiesis in the bone marrow caused by osteopetrosis, and the occurrence of extramedullary hemopoiesis in the spleen resulted in splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…In 2014, Katz et al . 3 reported a 52-year-old female osteopetrosis patient with portal hypertension who presented with ascites and esophageal variceal bleeding. The author believed that the cause of portal hypertension was the decreased hematopoiesis in the bone marrow caused by osteopetrosis, and the occurrence of extramedullary hemopoiesis in the spleen resulted in splenomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the third case was revealed by esophageal varices related hematemesis. This patient responded well to octreotide and later she was started on nadolol, furosemide and spironolactone for mild ascites [ 8 ]. In fact, several case reports of EMH associated PHT have been reported in literature.…”
Section: Discussionmentioning
confidence: 99%